"Be Like Living Stones": Remembering Philip Potter on the 100th Anniversary of His Birth. Issue 4 (26th October 2021) - Wartenberg‐Potter, Bärbel
Abstract: This is an edited translation of a tribute delivered in the Christuskirche, Cologne, on 22 August 2021 to mark the 100th anniversary of the birth of Philip Potter on 19 August 1921.